2020
DOI: 10.3390/jcm9092806
|View full text |Cite
|
Sign up to set email alerts
|

Craniocervical and Cervical Spine Features of Patients with Temporomandibular Disorders: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: To assess neck disability with respect to jaw disability, craniocervical position, cervical alignment, and sensorimotor impairments in patients with temporomandibular disorders (TMD), a systematic review and meta-analysis of observational studies trials were conducted. The meta-analysis showed statistically significant differences in the association between neck disability and jaw disability (standardized mean difference (SMD), 0.72 (0.56–0.82)). However, results showed no significant differences for cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 104 publications
1
17
0
3
Order By: Relevance
“…This is due to an altered neuro-biomechanical function of the cervical spine, which can apply stress on the TMJ, causing TMD. There is evidence to support that the craniomandibular region and upper cervical spine are related from anatomical, biochemical and neurophysiological standpoints [113,114], due to a neuroanatomical link between the orofacial and cervical regions, as well changes in the isometric strength of cervical flexors, according to the bite position of TMD patients [115,116]. Hence, the manual muscle test (MMT) is a reliable and useful clinical diagnostic tool for cervical muscles assessment to be considered [117].…”
mentioning
confidence: 99%
“…This is due to an altered neuro-biomechanical function of the cervical spine, which can apply stress on the TMJ, causing TMD. There is evidence to support that the craniomandibular region and upper cervical spine are related from anatomical, biochemical and neurophysiological standpoints [113,114], due to a neuroanatomical link between the orofacial and cervical regions, as well changes in the isometric strength of cervical flexors, according to the bite position of TMD patients [115,116]. Hence, the manual muscle test (MMT) is a reliable and useful clinical diagnostic tool for cervical muscles assessment to be considered [117].…”
mentioning
confidence: 99%
“…This monitoring is important since several studies have shown that an altered craniocervical posture seems to influence the process of myofascial pain sensitization in the cervical muscles, which could lead to the development of the referenced pain in the masticatory muscles [ 46 , 63 , 79 , 80 ]. Moreover, a recent systematic review and meta-analysis found that there was a significant correlation with a moderate clinical effect between neck disability and jaw disability in patients with TMDs [ 40 ]. In addition, a recent review by Gil-Martínez et al [ 39 ] reported that neck disability was a strong predictor of craniofacial pain and disability in a subgroup of patients with TMDs due to muscle pain and that neck disability has a positive correlation with orofacial pain and disability, kinesiophobia, and pain catastrophizing.…”
Section: Discussionmentioning
confidence: 99%
“…Taking this into account, it seems possible that the mechanical effects from orthodontics may lead to muscular and articular adaptations on the cervical spine. Furthermore, considering that a craniocervical dysfunction may act as a contributing factor to TMDs [ 15 , 25 , 26 , 28 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], it is reasonable to assume that the clinician should evaluate any change in the craniocervical region during orthodontic treatment, as well as any change in the TMDs complaints.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there was a coexisting reduction in the range of motion of the temporomandibular joint [30][31][32].…”
Section: Methodsmentioning
confidence: 99%